Effect of microwave heating on oxidative degradation of sunflower oil in the presence of palm olein - Abbas Ali, M.; Bamalli Nouruddeen, Z.; Ida I. Muhamad,; Abd Latip, R.; Hidayu Othman, N. (Universiti Kebangsaan Malaysia, 2014)
The aim of this study was to evaluate on how heat treatments by microwave oven may affect the oxidative degradation of sunflower oil (SFO) and its blend with palm olein (PO). The blend was prepared in the volume ratio of 40:60 (PO: SFO, PSF). The samples were exposed to microwave heating at medium power setting, for different periods. In this study, refractive index, free fatty acid content, peroxide value, p-anisidine value, total oxidation (TOTOX), specific extinction, viscosity, polymer content, polar compounds and food oil sensor value of the oils all increased, whereas iodine value and C18:2/C16:0 ratio decreased as microwave heating progressed. Microwave heating temperature increased with increasing heating time and longer heating times resulted in a greater degree of oil deterioration. The percentage of linoleic acid tended to decrease, whereas the percentage of palmitic acid increased. The effect of adding PO to SFO on the formation of free fatty acids and conjugated dienes during microwave treatment was not significant (p< 0.05). No significant differences in food oil sensor value was observed between SFO and PSF. Based on the most oxidative stability criteria, it can be concluded that the microwave heating caused the formation of comparatively lower amounts of oxidation products in PSF compared to SFO, indicating a lower extent of oxidative degradation of PSF.